Child development with the D-score: turning milestones into measurement [version 2; peer review: 1 approved, 2 approved with reservations] - Stef van Buuren; Iris Eekhout (Gates Open Research)
The chapter equips the reader with a basic understanding of robust psychometric methods that are needed to turn developmental milestones into measurements, introducing the fundamental issues in defining a unit for child development and demonstrates the relevant quantitative methodology. It reviews quantitative approaches to measuring child development; introduces the Rasch model in a non-technical way; shows how to estimate model parameters from real data; puts forth a set of principles for model evaluation and assessment of scale quality; analyses the relation between early D-scores and later intelligence; and compares the D-scores from three studies that all use the same instrument.